Biodegradable scaffolds based on plant stems for application in regenerative medicine - Ferranti, Carolina Costa; Alves, Eduardo Donato; Lopes, Camila Soares [UNESP]; Montrezor, Luís Henrique; Carvalho, Antonio José Felix; Cerri, Paulo Sérgio [UNESP]; Trovatti, Eliane (IOP Publishing, 2023)
Several synthetic and natural materials have been studied for the confection of temporary grafts for application in regenerative medicine, however, the development of a material with adequate properties remains a challenge, mainly because its degradation kinetics in biological systems. Nature provides materials with noble properties that can be used as such for many applications, thus, taking advantage of the available morphology and assembled structures of plants, we propose to study the vegetable stems for use as temporary graft. Since the in vivo degradation is maybe one of the most important features of the temporary grafts, here we have implanted the plant stems from pumpkin, papaya, and castor into the subepithelial tissue of animals and followed their biodegradation process and the local inflammatory response. Mechanical tests, FTIR and contact angle with water were also analysed. The results indicated the mechanical properties and the contact angle were adequate for use in regenerative medicine. The results of the in vivo studies indicated a beneficial inflammatory process and a gradual disintegration of the materials within 60 days, suggesting the plants stems as new and potential materials for development of grafts for use in the field of regenerative medicine.
Keywords: carica papaya L; cucurbita máxima L; In vivo degradation; ricinus communis L; temporary vegetable scaffolds